THE SALIVARY BONE SPESIFIC ALKALINE PHOSPHATASE IN RELATION TO PUBERTAL GROWTH PHASE IN INDONESIAN CHILDREN - Wijaya, Harryanto; Kusdhany, Lindawati S; Redjeki, Sri; Soegiharto, Benny M (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To evaluate the level of salivary Bone specific Alkaline Phosphatase (BALP) during the pubertal growth phases in Indonesian Children. Materials and Methods: The study conducted on 64 boys and 72 girls who were age group of 8 â€“ 18 years old were randomly selected. Salivary BALP level was estimated using Enzyme-Linked Immunosorbent Assay (ELISA) commercial kits and pubertal growth phase were assessed using Cervical Vertebral Maturation (CVM) method according to Baccetti. Mean salivary BALP were compared based on pubertal growth groups by Analysis of Variance (ANOVA) test. Results: Test revealed no significant differences between groups with p value 0.312. The highest mean of salivary BALP level was found in the pre peak pubertal growth phase (CVM stage 1-2) and the lowest one was detected in the post peak pubertal growth phase (CVM stage 5-6). Conclusion: The using of salivary BALP as a biomarker for pubertal growth prediction is questionable. Â 